A stable isotope and functional weed ecology investigation into Chalcolithic cultivation practices in Central Anatolia: Çatalhöyük, Çamlıbel Tarlası and Kuruçay. (August 2021) - Stroud, Elizabeth; Bogaard, Amy; Charles, Michael
Highlights: First multi-proxy research into crop husbandry during the Anatolian Chalcolithic. Functional ecology indicates variable crop husbandry intensities at Çatalhöyük West. Consistent, less variable crop husbandry conditions at the Late Chalcolithic sites. Cultivation of barley in drier locations compared to the other crops at Çatalhöyük. Environment, site size and settlement date key factors in shaping crop husbandry. Abstract: The integration of stable isotope analysis of crop remains with the ecological analysis of archaeological weed flora allows for a detailed reconstruction of crop husbandry and arable growing conditions. This paper presents the first such study for developed Neolithic and Chalcolithic Central Anatolia, exploring crop husbandry at the large (8 ha) early 6th millennium BC site of Çatalhöyük West and the last phases of the preceding Neolithic Çatalhöyük East, located on the western end of the Konya Plain, and the small 4th millennium sites of Çamlıbel Tarlası (0.25 ha), located in the loop of the Kızılırmak river, and Kuruçay Höyük (~1 ha), located on the shore of Lake Burdur. The results reveal the mosaic nature of Çatalhöyük cultivation; the complex ecosystem, naturally 15 N enriched, was additionally anthropogenically improved, while inhabitants also chose to cultivate barley in drier conditions to the wheats and pulses. The smaller, Late Chalcolithic site of Çamlıbel Tarlası cultivated each individual crop species in variable conditions instead of selecting a specific species for cultivation in drier or wetter conditions. Each single species was cultivated in conditions with a wide range of water availabilities while receiving low-level manure application. Variation in water availability is possibly a consequence of the variable topography surrounding the site, with the hills potentially used for cultivation, providing a wide range of conditions due to their slope. Functional weed ecology complements the isotopic data, indicating the wider range of cultivation intensities surrounding Çatalhöyük West, compared with more consistent, narrower ranges of growing conditions at Çamlıbel Tarlası and Kuruçay Höyük. Settlement date, site size and environment seem to be key contributing factors shaping the method used to cultivate crops at these Chalcolithic sites. The larger, earlier community of Çatalhöyük West, located in a complex riverine ecosystem around the dryland anabranching channels of the Çarşamba river, cultivated species in different conditions and maintained a range of crop husbandry intensities, potentially reflecting differential access to limited resources. The smaller Late Chalcolithic sites, with communities consisting of one household to several households and located in less complex ecosystems with higher precipitation, maintained more stable crop growing conditions and management intensities. This is plausibly a consequence of equal access and sharing of critical resources for crop cultivation, such as labour, manure and land, coupled with the adequate precipitation rates.